Penguatan Kapasitas Lembaga Kemasyarakatan Desa (LKD) dalam Mendukung Pembangunan Desa Pamboborang Kecamatan Banggae, Kabupaten Majene - Danar Hafidz Adi Wardhana; Achmad Fauzi Kusmin; Muhammad Sajidin; Riady IK (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Village Community Institutions (LKD) play a strategic role in supporting village governance and the implementation of community-based development. However, various challenges remain for many LKDs, particularly in terms of institutional capacity, regulatory understanding, and collaboration among stakeholders. This community service activity aims to strengthen the capacity of the LKD of Pamboborang Village, Banggae Sub-District, Majene Regency, in supporting sustainable village development. The activity was conducted through interactive lectures focusing on improving understanding of institutional functions, strategic roles in planning and monitoring development, and the importance of synergy between the LKD, village government, and the community. Participants included LKD members, village officials, and local community representatives. The results showed an increase in participants’ understanding of the main duties and functions of LKDs, along with a growing collective awareness of the importance of local institutional roles in sustainable development. This activity serves as a tangible contribution to transforming village governance through institutional empowerment. In the future, follow-up actions such as continuous mentoring and practice-based training will be needed so that LKD institutional capacity can develop systematically and independently.